2022
DOI: 10.3389/fpubh.2022.1017718
|View full text |Cite
|
Sign up to set email alerts
|

Application of multiple occupational health risk assessment models in the prediction of occupational health risks of n-Hexane in the air-conditioned closed workshop

Abstract: Backgroundn-Hexane (NH) poisoning is a common occupational poisoning in the hardware and electronics industries. However, there is few research data on risk assessment of positions using NH in enclosed workshops. It is very important to assess the risk level of these positions and put forward effective measures and suggestions.MethodsThe information of selected companies and air samples were collected through on-site investigation, and data collation and sample testing were carried out according to the require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Also, Cohen's Kappa displayed that there is a good consistency between Malaysia method/GBZ/T 298-2017 (K = 0.951) and COSHH model/GBZ/T 298-2017 (K = 0.867) (Table 5). Zhu et al showed that there is a good consistency between Malaysia or Singapore model and the Chinese Exposure Index method (GBZ/T 298-2017) and Singapore moled and the Synthesis Index method (Zhu et al 2022). As mentioned earlier, the GBZ/T 298-2017 is a comprehensive risk assessment based on the COSHH model and the Malaysia model.…”
Section: The Concentration Of Welding Fumesmentioning
confidence: 99%
“…Also, Cohen's Kappa displayed that there is a good consistency between Malaysia method/GBZ/T 298-2017 (K = 0.951) and COSHH model/GBZ/T 298-2017 (K = 0.867) (Table 5). Zhu et al showed that there is a good consistency between Malaysia or Singapore model and the Chinese Exposure Index method (GBZ/T 298-2017) and Singapore moled and the Synthesis Index method (Zhu et al 2022). As mentioned earlier, the GBZ/T 298-2017 is a comprehensive risk assessment based on the COSHH model and the Malaysia model.…”
Section: The Concentration Of Welding Fumesmentioning
confidence: 99%